Employing Picture Description to Assess the Students' Descriptive Paragraph Writing - Ida Ayu Mega Cahyani; Ida Bagus Nyoman Mantra; I Gusti Agung Putri Wirastuti (Politeknik Negeri Bali, 2018)
Writing is considered as an important skill in learning process which is needed to be mastered by the students. However, in teaching learning process at schools or universities, the assessment of writing skill is not becoming the focus of learning process and the assessment is administered inappropriately. In this present study, the researcher undertook the study which dealt with assessing descriptive paragraph writing ability of the students through picture description by employing an ex post facto as the research design. The present study was intended to answer the research problem dealing with the extent of the students’ achievement of descriptive paragraph writing ability which is assessed through picture description. The samples under the study were 40 students determined by means of random sampling technique with lottery system. The data were collected through administering picture description as the research instrument. The obtained data were analyzed by using norm-reference measure of five standard values. The results of the data analysis showed that there were 67.50% samples of the study were successful in writing descriptive paragraph, while there were 32.50% samples were unsuccessful in writing descriptive paragraph which was assessed by administering picture description test